Fabrication, Microstructure, Hardness and Magnetic Properties of (W:Ti)C-Ni Cemented Carbides using Atomized Ni powder (Global Journals of Research in Engineering, 2018)
(W:Ti)C cemented carbides with different Ni content fabricated by powder metallurgy technique were investigated. The Ni powder which used as a metal binder of the (W:Ti)C-Ni abrasive particles was fabricated by water atomization technique by means of induction furnace. A Ni powder of a cubical particle shape with average particle size of 2-20 #x3BC;m was obtained. Six (W:Ti)C-Ni compositions with Ni contents of 5, 10, 15, 20, 25 and 30 wt.% were prepared by mechanical milling of the obtained atomized Ni powder with the abrasive (W:Ti)C particles followed by cold compaction at 600 MPa and vacuum sintering at 1450oC. Dense (W:Ti)C-Ni cemented carbides were obtained with a relative density of up to 94% with 30 wt% Ni. The hardness of the dense (W:Ti)C#x2013;30 wt.%Ni was greater than the hardness of other different compositions; The magnetic properties, which were measured at an applied field of 2tesla, indicate that the (W:Ti)C#x2013;Ni cemented carbides have ferromagnetic properties with a higher mass saturation magnetization with higher nickel content
Keywords: Fabrication; Microstructure; Hardness and Magnetic Properties of (W:Ti)C-Ni Cemented Carbides using Atomized Ni Powder